Markups, organic agriculture and downstream concentration at the example of European dairy farmers - Maximilian Koppenberg (Agricultural Economics, 2023)
A competitive environment, highly concentrated processing and retailing sectors as well as increasing decoupling of direct payments from production volumes and the area under cultivation incentivizes farmers to find alternative ways to improve their bargaining position towards downstream companies. This article explores the possibilities of organic agriculture to enhance the bargaining power of farmers along with the role of concentration in downstream industries. Using a dataset with more than 200,000 observations from approximately 40,000 dairy farms, I estimate markups of price over marginal cost in dairy farming as a measure of market power in the EU. The results show that organic farmers achieve a significant markup premium over conventional farmers. With increasing market shares of organic milk in total milk production markups of conventional farmers diminish whereas those of organic farmers are unaffected. Farm-level markups decrease with increasing market shares of medium-sized dairy processors and increase with increasing market shares of large processors. The presence of large multinational retail chains shows an adverse impact on farmers' markups.
Keywords: 330; dairy farming; market power; markups; organic agriculture